Cross-Sectional Associations of Environmental Perception with Leisure-Time Physical Activity and Screen Time among Older Adults - Hsueh, Ming-Chun (J Clin Med, 2018)
This study investigated associations of perceived environmental factors with leisure-time physical activity (LTPA) and screen time (ST) among older adults. A cross-sectional study was conducted by administering computer-assisted telephone interviews to 1028 older Taiwanese adults in November 2016. Data on personal factors, perceived environmental factors, LTPA, and ST were included. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to examine associations of environmental perception with LTPA and ST by using logistic regression analyses. The results showed that after adjusting for potential confounders, older adults who perceived their neighborhood with good access to shops (AS) and to public transportation (AT) were more likely to have sufficient LTPA (AS: OR = 1.64, 95% CI: 1.16–2.32; AT: OR = 1.43; 95% CI, 1.00–2.03) and less likely to have excessive ST (AS: OR = 0.70; 95% CI: 0.50–0.97; AT: OR = 0.64; 95% CI: 0.46–0.90). Different perceived environmental factors were also associated with LTPA and ST, respectively. This study highlights environment perception as a crucial factor for LTPA and ST. These findings suggest that policy makers and physical activity intervention designers should develop both common and individual environmental strategies to improve and increase awareness of the neighborhood environment to promote LTPA and reduce ST among older adults.